Gerontius - Hamilton-Paterson, James (Vintage, 1990)
The starting point of this novel is an event in the life of Sir Edward Elgar - a cruise to the Amazon that he took in 1923. In telling the story of that journey the author explores melancholy, the waning of creative genius, post-war disillusionment and the way in which England treats its artists.